Limiting sovereignty or producing governability? Two models of human rights in the political discourse of the United States - Guilhot, Nicolas (Política. Revista de Ciencia Política, 2011)
The sociology of international activism has often focused on human rights in order to illustrate the ‘power of ideas’ in the design of public policy. According to this view, the successful institutionalization of human rights principles under the Carter administration forced the Reagan administration to adjust its policies to principles it could neither ignore nor use for purely instrumental purposes. The paper argues that these approaches ignore the disputed and controversial nature of political-legal concepts and the fact that their very definition is at stake in struggles between competing sets of actors seeking to use these concepts to legitimate different policy approaches. Mapping out the field of producers of the human rights discourse in the late 1970s-early 1980s, both in their civil and governmental components, the paper shows that the concept of human rights has been constructed along two main principles, each corresponding to specific social and political interest groups. The first bases human rights in international law and is promoted mainly by lawyers and activists linked to international organizations. The second, conceived mainly by neoconservatives, has an anti-legal approach to the concept of human rights, linking it instead to democracy promotion.